(untitled) (Research, Society and Development, 2021)
The purpose of this article is to review the literature on the essential technical aspects of implementing the pulsed Doppler, as part of the teachings to their use in the diagnosis of changes in the canine reproductive system. A narrative review was carried out, using scientific articles, monographs, theses and dissertations published and available in online databases: Periodical Capes (Coordination for the Improvement of Higher Education Personnel), SciELO (Scientific Electronic Library Online) and Google Scholar, in addition to specific books on the topic. Two-dimensional ultrasound has been widely used in medicine since 1942, leading to advancements in disease identification and subsequent prognosis. In terms of vascular assessment, Doppler ultrasound is used to evaluate the blood flow inside the vessel, its direction, and hemodynamic pattern. Among all types of Doppler ultrasound, the Color Doppler (CD), Power Doppler (PD), and the Pulsed-wave Doppler (PW) are commonly used in the identification of abnormalities through ultrasound flow imaging and the analysis of hemodynamic indices: peak systolic velocity (PSV), end diastolic velocity (EDV), resistance index (RI), and pulsatility index (PI). To accurately estimate these hemodynamic indices, however, it is essential to know the technical adjustments and parameters such as the pulse repetition frequency (PRF), size of the sample volume (Gate), angle of insonation, gain, baseline, and wall filter, which need to be corrected to avoid technician derive artifacts such as aliasing, signal absence, and mirror imaging. In medicine, the use of Doppler Mode in reproductive functions is already well established, but its use in veterinary medicine is still a subject of recent studies.